Ethnobotanical study of medicinal plants in Asagirt District, Northeastern Ethiopia - Tahir, Muhidin; Asnake, Hiwot; Beyene, Tadesse; Van Damme, Patrick; Mohammed, Amin (Tropical medicine and health, 2023)
BACKGROUND: The people in Ethiopia have developed their own specific knowledge to use, manage and conserve plant resources, giving traditional medicine its diverse nature. Documenting and investigating the traditional and cultural use of remedial plants is vital to extract bioactive chemicals and preserve plant species. This research was conducted with the aim of documenting ethnobotanical and associated knowledge on medicinal plants in Asagirt District, northeastern Ethiopia. METHODOLOGY: The study was conducted from September 27, 2018, to April 9, 2019. A total of 367 informants (244 males and 123 females) were involved in the interviews. General informants (n = 349) were randomly selected, whereas key informants (n = 18) were selected purposively. Data were collected by using semistructured interviews, group discussions and guided field walks. We performed direct matrix ranking and preference ranking, and calculated the fidelity level and informant consensus factor (ICF). Descriptive statistics, including analysis of variance (ANOVA) and independent sample t-test were used to analyse the data. RESULTS: Overall, 103 medicinal plant species belonging to 96 genera under 45 plant families were recorded to be used by Asagirt people to alleviate different health problems. The species used to heal human diseases only were (64%, 66 species) followed by both livestock and human ailments (31%, 32 species) and livestock diseases only (5%, 5 species). Asteraceae and Fabaceae were best-represented (10.7%, 11 species each). The most frequently used plant parts were leaves (28%, 29 species), followed by seeds (16%, 17 species). The most important method of herbal remedy preparation was crushing (20.4%, 21 species). The common route of administration was oral (46.6%, 48 species), followed by dermal (22.3%, 23 species). Febrile illness, fever, headache, amoebiasis, typhoid and diarrhoea ailment categories had the highest ICF value (0.99). Ocimum lamiifolium Hochst. ex Benth. scored the maximum fidelity level value (98%). CONCLUSION: Asagirt District is comparatively rich in medicinal plants and their associated knowledge. However, firewood collection, construction, the expansion of agricultural activities and timber production are the major challenges to medicinal plants. Hence, joint management with the people in Asagirt District in overall medicinal plant conservation would save medicinal plant resources.
Keywords: Ethiopia; Asagirt District; Ethnobotany; Indigenous knowledge; Conservation; Medicinal plants